ANALISIS PENERAPAN PAJAK PENGHASILAN PADA PT. ENSEVAL PUTERA MEGATRADING Tbk - Prasetya, Agung; ., Suhendro; Dewi, Riana R (Prosiding Seminar Nasional: Manajemen, Akuntansi, dan Perbankan; Vol 1 No 1 (2018): Prosiding Seminar Nasional dan Call for Papers Manajemen, Akuntansi, dan Perbankan 2018, 2018)
The purpose of this research is to find out and analyze the application of income tax at PT. Enseval Putera Megatrading Tbk. This study uses descriptive qualitative research. The object of this research is PT Enseval Putra Megatrading Tbk. The analysis technique of this research uses comparative descriptive analysis. Data collection techniques are observation and interview. The results showed that the analysis of calculation, deduction, payment and reporting of Article 21 PPh at PT Enseval Putera Megatrading Tbk was in accordance with the law and there was no difference in calculation between the company and the researcher. Analysis of calculation, deduction, payment and reporting of Article 22 PPh to PT Enseval Putra Megatrading Tbk is in accordance with the law. Although there is a very small difference between companies and researchers. This happened because of the basic calculation of Article 22 Income Tax. Analysis of calculation, deduction, payment and reporting of Article 23 PPh at PT Enseval Putra Megatrading Tbk was in accordance with the law and there was no difference in calculation between the company and the researcher.